1995
DOI: 10.1139/x95-038
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in the Bight environment of developing Scots pine stands: the basis for a quick and efficient method of characterizing Bight

Abstract: Spatial and temporal variations in photosynthetic photon flux density (PPFD) at 1 m above the forest floor were measured under and between dominant pines and in 21- to 52-m2 gaps under developing Scots pine (Pinussylvestris L.) stands in southern Finland. For each stand, PPFD data were collected continuously every 10-s and then averaged for every 5-min period during 4-6 days under completely clear and overcast sky conditions. Measurements were made during 102 consecutive days within two different areas in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 0 publications
5
110
2
1
Order By: Relevance
“…Light measurements were taken under completely overcast sky conditions following the method proposed by Messier and Puttonen (1995) and Parent and Messier (1996). These studies have shown that instantaneous measurements obtained under completely overcast sky conditions are a good estimate of the mean daily percent PPFD under both overcast and clear sky conditions.…”
Section: Characterizing the Light Environmentmentioning
confidence: 99%
“…Light measurements were taken under completely overcast sky conditions following the method proposed by Messier and Puttonen (1995) and Parent and Messier (1996). These studies have shown that instantaneous measurements obtained under completely overcast sky conditions are a good estimate of the mean daily percent PPFD under both overcast and clear sky conditions.…”
Section: Characterizing the Light Environmentmentioning
confidence: 99%
“…Cette proportion représentait la moyenne journalière de lumière incidente reçue à l'apex de l'arbre étudié (Messier et Puttonen 1995a).…”
Section: Mesures De Lumièreunclassified
“…Single measurements of light taken at midday in midsummer have been used widely to characterize light environments (Messier and Puttonen 1995;Parent and Messier 1996). Instantaneous measurements of transmittance on overcast days using single sensors show stronger correlation with growing season transmittance than do midday or entire-day measurements on sunny days (Messier and Puttonen 1995;Comeau et al 1998;Lieffers et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies comparing methods for estimating light under different types of stands (Messier and Puttonen 1995;Yanhong and Naoki 1997;Comeau et al 1998;Jennings et al 1999). Comeau et al (1998) found that growing season light under a paper birch mixedwood stand can be reasonably estimated using quantum sensors (>r=0.89), hemispherical photographs, and LAI-2000 plant canopy analyzers.…”
mentioning
confidence: 99%
See 1 more Smart Citation